Análise de retenção do escoamento superficial e desempenho térmico de telhado verde extensivo sobre telhado de fibrocimento - Santos, Carolina Pereira dos (2019)
Fiber cement tiles are widely used in building coverings because of its low cost and ease of installation. This type of roof cover allows the transmission of external and internal temperatures, causing the building to fail to fulfill part of its shelter function and to provide thermal comfort.Moreover, fiber cement tiles contribute to the rapid runoff of rainwater, wich can contribute to flooding problems in cities.In this sense, the aim of this work was to compare different types of treatments on fiber cement roofsfromthe standpoint of rainwater retention and thermal efficiency. The experiments were performed under natural conditions in the municipality of Dois Vizinhos-PR. The research was carried out in field scale, with nine roof modules on a bench, subjected to three different treatments: exposed fiber cement roof, expanded clay on fiber cement roof, and extensive green roof over fiber cement tiles.The chosen vegetation was Grama Missioneira (Axonopus sp). Theexperiment design was completelyrandomized. The data were collected in 25 independent rain events. The temperature data were collected at 7 a.m., 12 a.m., and 6 p.m., in the autumn, winter and spring seasons by using a surface measurement thermometer. The green roofs retained about 70% of the total precipitation. On the other hand, the expanded clay retained about 30%, andthe fiber cement tiles retained about 6% of the total precipitation. With regard to thermal performance, the green roofs were the most efficient. Moreover, the external temperature on the green roofs showed less variationwith 27,2ºC. The highest external temperature variation was observed on the expanded clay treatmentwith 47,9ºC. In conclusion, the green roofs can be used as an alternative in reducing runoff and in increasing the thermal efficiency of buildings.